Australian Enterococcal Sepsis Outcome Programme annual report, 2013 - Coombs, Geoffrey; Pearson, J.; Daly, D.; Le, T.; Robinson, J.; Gottlieb, T.; Howden, B.; Johnson, P.; Bennett, C.; Stinear, T.; Turnidge, J. (2014)
From 1 January to 31 December 2013, 26 institutions around Australia participated in the Australian Enterococcal Sepsis Outcome Programme (AESOP). The aim of AESOP 2013 was to determine the proportion of enterococcal bacteraemia isolates in Australia that are antimicrobial resistant, and to characterise the molecular epidemiology of the Enterococcus faecium isolates. Of the 826 unique episodes of bacteraemia investigated, 94.6% were caused by either E. faecalis (56.1%) or E. faecium (38.5%). Ampicillin resistance was not detected in E. faecalis but was detected in over 90% of E. faecium. Vancomycin non-susceptibility was reported in 0.2% and 40.9% of E. faecalis and E. faecium respectively and was predominately due to the acquisition of the vanB operon. Overall, 41.6% of E. faecium harboured vanA or vanB genes. The percentage of E. faecium bacteraemia isolates resistant to vancomycin in Australia is significantly higher than that seen in most European countries. E. faecium isolates consisted of 81 pulsed-field gel electrophoresis pulsotypes of which 72.3% were classified into 14 major pulsotypes containing five or more isolates. Multilocus sequence typing grouped the 14 major pulsotypes into clonal cluster 17, a major hospital-adapted polyclonal E. faecium cluster. Of the 2 predominant sequence types, ST203 (80 isolates) was identified across Australia and ST555 (40 isolates) was isolated primarily in the western and central regions (Northern Territory, South Australia and Western Australia) respectively. In conclusion, the AESOP 2013 has shown enterococcal bacteraemias in Australia are frequently caused by polyclonal ampicillin-resistant high-level gentamicin resistant vanB E. faecium, which have limited treatment options.